Esophageal lichen planus: towards diagnosis of an underdiagnosed disease. (3rd October 2019) - Schauer, Franziska; Monasterio, Carmen; Technau-Hafsi, Kristin; Kern, Johannes Steffen; Lazaro, Adhara; Deibert, Peter; Hasselblatt, Peter; Schwacha, Henning; Heeg, Steffen; Brass, Volker; Küllmer, Armin; Schmidt, Arthur Robert; et al.
Abstract: Background: Although lichen planus (LP) is a common skin disorder, the prevalence of esophageal involvement (ELP) and its clinical manifestations are poorly defined. We aimed to establish diagnostic criteria and characterize disease outcomes of ELP. Methods: Clinical, endoscopic, histological, and immunofluorescence data from consecutive patients with known LP between 2013 and 2018 were analyzed. We established endoscopic (denudation and tearing of the mucosa, hyperkeratosis and trachealization) and histological criteria (mucosal detachment, T-lymphocytic infiltrate, intraepithelial apoptosis, dyskeratosis, and fibrinogen deposits along the basement membrane) to grade disease severity. Endoscopic findings were correlated with clinical symptoms. Response to medical therapy was monitored. Results: Fifty-two consecutive patients (median age 59.5 years) were analyzed. According to our grading system, 16 patients were considered as severe and 18 as mild ELP. Dysphagia was the only symptom which differentiated patients with severe (14/16) or mild ELP (8/18) from patients without ELP (1/18). Concomitant oral and genital involvement of LP was associated with the presence of ELP, while oral involvement alone was not. Follow-up of 14/16 patients with severe EPL for at least one year revealed that most of these patients responded to topical corticosteroids (budesonide: n  = 9/10 or fluticasone n  = 2/2). Three budesonide patients experienced a resolution of symptomatic esophageal stenosis. Conclusions: Esophageal involvement of LP is frequent, but may be asymptomatic. ELP can be diagnosed using the diagnostic criteria proposed here. Dysphagia and combined oral and genital manifestation are associated with ELP. Therapy with topical corticosteroids appears to be a prudent therapeutic approach for ELP.